Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
Accepted: 2022-05-18T23:30:06Z Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.84697 2405685:8XW8JR6H

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7054334 ZenodoArchiveConcept: 7054333 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7054334 10.53832/edtechhub.0126 2405685:GQSKFD62 2405685:XLXRPW3Z
Keywords: _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13255974 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1052 ZenodoArchiveConcept: 13255973
Keywords: _r:AddedByMyEducationEvidence

What is 'Nudging' and How Does it Change Behaviour in Education? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the behaviour change strategy of leveraging concise messages at strategic decision points (i.e., ‘nudging’) to influence the behaviour of a recipient towards a desired outcome. We focus on EdTech Hub’s work concerning nudge messaging. It builds on work from messaging interventions in Ghana and Kenya, linking these to the broader literature on the topic. It emphasises that although there is a strong and growing evidence base for nudge technologies, effective implementation remains dependent upon context-specific adaptation. It is not inevitable that nudge messaging interventions will lead to positive outcomes — indeed, outcomes are often mixed. It is therefore vital to understand the specific impacts of interventions on particular groups of recipients. We present findings and recommendations that should inform how nudging technologies in education are approached and what decision-makers need to consider in order to ensure uptake and minimise risks. Lastly, we explore areas that require further research, namely, the changing nature of nudging due to artificial intelligence, the safeguarding risks of nudging, persisting questions about cost-effectiveness, and how nudging can more specifically target learning. Keywords: Behavioural psychology; EdTech; education; messaging; nudging; participation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10628960 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1011 ZenodoArchiveConcept: 10628959
Keywords: _r:AddedByMyEducationEvidence

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Supporting Head Start parents: impact of a text message intervention on parent–child activity engagement - Hurwitz, Lisa B.; Lauricella, Alexis R.; Hanson, Ann; Raden, Anthony; Wartella, Ellen (Early Child Development and Care, 2015)
Head Start emphasises parent engagement as a critical strategy in promoting children's long-term learning. Parents can support children's positive development by engaging them in stimulating activities. The following study assessed whether a service that delivered parenting tips via text message could prompt parents of children enrolled in Head Start programmes to engage in more learning activities with their children. Two hundred and fifty-six parents participated in the study with approximately half receiving text messages for six weeks. All participants completed a questionnaire about the types of learning activities in which they engaged their children. Parents who received the service engaged in more learning activities; this was particularly true of fathers and parents of boys. Parents reported high rates of satisfaction with service. These results suggest that text-based interventions as a supplement to other forms of family engagement may successfully communicate parenting information and support parental engagement with young children.
Publisher: Routledge _eprint: https://doi.org/10.1080/03004430.2014.996217 KerkoCite.ItemAlsoKnownAs: 10.1080/03004430.2014.996217 2339240:NJTXLNF5 2339240:TK28IPXS 2405685:F9LQR8ZG 2405685:Q6CYNMQT 2405685:UM843NTW 2534379:P9HM3PMZ
Keywords: Head Start; ___working_potential_duplicate; activities; early childhood; intervention; parenting; text messaging

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6337916 10.5281/zenodo.6337918 10.5281/zenodo.6338002 10.5281/zenodo.6338007 10.53832/edtechhub.0083 2339240:AZXVF44M 2339240:GZRZGRN7 2339240:MJPJVVCU 2405685:6QCZIQR2 2405685:D9VW8AI3 2405685:PWU63GQS 2405685:QAXG3NCJ 2405685:RKRPWPX5 2405685:VT5Z6XB6 2405685:YBG8MTTQ 2405685:ZDHGEBKD
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5849102 10.53832/edtechhub.0071 2339240:5YT7LKSS 2405685:6FN5VTP7 2405685:8UMQILZ9 2405685:GMA7II34 2405685:WEG87IDU
Keywords: _r:AddedByZotZen

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5032936 10.5281/zenodo.5142392 10.53832/edtechhub.0094 2405685:G9DHSZ57 2405685:HL6BNMQZ
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5774707 10.53832/edtechhub.0093 2339240:SCCGE8HG 2405685:HEXCEXFK 2405685:NBAIXDE4 2405685:XMGEKJ3V
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech Horizon Scan: Rapid scan of online safety in education - Mazari, Haani; Kaye, Tom (EdTech Hub, 2022)
This EdTech Horizon Scan examines the issue of online safety in digital education — why it should be prioritised, how it is currently being approached, and its potential to become central to education design in low- and middle-income countries. Given that the internet has no borders, there is much to be done to address online safety in all parts of the world — high-income and low- and middle-income countries alike. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7336710 ZenodoArchiveConcept: 7336709 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7336710 10.53832/edtechhub.0136 2339240:4TCBX2GH 2405685:3QBCENK5 2405685:AWHK2L8L
Keywords: _r:AddedByZotZen

Using EdTech in Response to Climate Emergencies in Pakistan - Hayat, Amal; Mazari, Haani; Aslam, Nawaz (EdTech Hub, 2025)
This policy brief explores how EdTech can support a climate-resilient education system, drawing on insights from stakeholder consultations and EdTech Hub's research on learning continuity in response to climate emergencies following the 2022 Pakistan floods. While recovery efforts often focus on restoring physical infrastructure, we argue that a shift to long-term resilience against climate emergencies can be supported by strategic and contextually relevant use of EdTech. The brief highlights the importance of addressing the evolving needs of learners and teachers across all phases of emergencies through preparedness measures and cross-sectoral collaboration. Keywords: Pakistan floods; climate resilience; EdTech; Education in emergencies; South Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15851578 ZenodoArchiveConcept: 15851577 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7782171 10.53832/edtechhub.0160 10.53832/edtechhub.1129 2405685:333BJPIR
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

Optimising Messaging to Promote Returns to School in Ghana for Marginalised Learners - EdTech Hub (EdTech Hub, 2021)
ZenodoArchiveID: 5596883 ZenodoArchiveConcept: 5596882 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0058 2405685:DMVKGJWQ

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
ZenodoArchiveID: 5652128 previousZenodoArchiveID: 3885817 previousshortDOI: 10/ghgngv previousshortDOI: 10/ghgngv previousDOI: 10.5281/zenodo.3885817 previousshortDOI: 10/ghgngv EdTechHub.Source: 2405685:HE2Q6Z8Y EdTechHub.Source: <this> shortDOI: 10/ghgngv KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3885817 10.53832/edtechhub.0018 10/ghgngv 2129771:YC82FCEP 2339240:TND87RAP 2405685:HE2Q6Z8Y 2405685:SRU74BP6
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:6HPRIAVP 2339240:7C7I9C4I 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:4MGG3JS3 2405685:5U948655 2405685:6UZHTZ8G 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Using Mobile Phone Texting to Support the Capacity of School Leaders in Ghana to Practise Leadership for Learning - Swaffield, Sue; Jull, Stephen; Ampah-Mensah, Alfred (Procedia - Social and Behavioral Sciences, 2013)
Several years into a collaborative professional development programme to build the Leadership for Learning capacity of Basic school headteachers throughout Ghana, the challenge is to sustain commitment, deepen understanding and share learning among the school leaders. Employing ubiquitous mobile phone technology, weekly text messages have been sent to the programme's 175 initial participants. During the year of the pilot project different forms of messages have been tried, and feedback from recipients suggests their value. The paper reports experience and findings from the pilot, and considers plans for scaling-up to reach all 18,000 Basic schools across the country.
shortDOI: 10/gf7gsh KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2013.10.459 10/gf7gsh 2339240:6QNXM9T9 2339240:C993QBLL 2405685:38U7QI2P 2405685:V3PRBKSK 2405685:XNAPWJG9 2405685:XNBYZ9E9
Keywords: Ghana; Leadership for Learning; SMS; headteachers; mobile phone; professional development; school leaders; text messages

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0080 2339240:PRMHXVPE 2405685:7S9CUP77 2405685:HHXQI3S4 2405685:VU5JQKWG 2534378:BXN59IRN
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7065183 ZenodoArchiveConcept: 7065182 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7065183 10.53832/edtechhub.0142 2339240:HPTMF4RJ 2405685:2437EGZU 2405685:UCMLR25N
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
previousshortDOI: 10/ghgng5 previousDOI: 10.5281/zenodo.3762228 EdTechHub.Copy: 2129771:QQWNSYJR EdTechHub.Copy: 2129771:QQWNSYJR shortDOI: 10/ghgng5 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3762228 10.53832/edtechhub.0022 10/ghgng5 2129771:QQWNSYJR 2339240:45F2G56T 2405685:3MKIMX34 2405685:A3T2DQ4D 2405685:WB97BS9V
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
00000 EdTechHub.Source: 2129771:D2GQYC5S KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v5i1.264 2129771:43ZT3XWL 2129771:52KKAHKR 2129771:AAT7FR3H 2129771:D2GQYC5S 2129771:LDWSNI7T 2129771:LHMXV7QF 2249382:CS9PALG8 2317526:6IH7CD39 2317526:PP4CHVEG 2339240:2BCABLG6 2339240:4N3G4XDJ 2339240:9BPXVI62 2339240:C7CKIPL7 2339240:D83N6FTA 2339240:HGHAYJ5G 2339240:HR2YGWX3 2339240:P65I7MGU 2339240:YSVITTWH 2405685:3GSCKVWC 2405685:7X2D9JDG 2405685:CUHYHFLV 2405685:M8UDHT7A 2405685:NKSYKNQN 2405685:NVEVT9HX 2405685:NZ3GKZCR 2405685:T2I86FZT 2405685:ZFJ79LQS 2486141:Z3PRLX4K 257089:AJJPQKDF 261451:JC3NQMN3 261495:BWD9L8FL 261495:TCP47GGI
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3878423 previousshortDOI: 10/ghgk6n previousshortDOI: 10/ghgk6n previousDOI: 10.5281/zenodo.3878423 previousshortDOI: 10/ghgk6n EdTechHub.Source: 2405685:DS66UGW4 EdTechHub.Source: <this> shortDOI: 10/ghgk6n KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3878423 10.53832/edtechhub.0019 10/ghgk6n 2129771:GKIQY5RP 2339240:29BIZJM5 2339240:WSA5X76N 2405685:4Z5W36SI 2405685:DS66UGW4 2405685:IS587WTH
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10604329 ZenodoArchiveConcept: 10604328 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10080685 10.53832/edtechhub.1005 2405685:GXMUGXHE 2405685:RK44C9BZ
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
ZenodoArchiveID: 4928926 PreviousDOI: 10.5281/zenodo.4747301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4928926 2339240:PXT8SGSZ 2405685:9P9W4I53 2405685:A2D9FVTA 2405685:C2579UKC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Publisher: Wiley-Blackwell, 350 Main Street, Malden, MA 02148 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013524047?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12571 2339240:PKJIVPW8 2405685:EPP6N37E 2405685:IARRK6UB 2534378:L8X5Q62N 2534378:UH8EAVTI 2534378:UIYLRWUW
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction–CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

A tale of two communication tools: discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2018)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
Publisher: Wiley-Blackwell, 350 Main Street, Malden, MA 02148 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013524047?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12571 2339240:PKJIVPW8 2405685:EPP6N37E 2405685:IARRK6UB 2534378:L8X5Q62N 2534378:UH8EAVTI 2534378:UIYLRWUW
Keywords: Applications programs; China; Collaborative learning; Collaborative virtual environments; Communication; Computer Mediated Communication; Computer Software; Computer assisted instruction–CAI; Content Analysis; Content analysis; Cooperative Learning; ERIC; Current Index to Journals in Education (CIJE); Education–Teaching Methods And Curriculum; Educational technology; Foreign Countries; Handheld Devices; Higher Education; Learning; Network Analysis; Network analysis; Preferences; Preservice Teachers; Social Networks; Social factors; Student Attitudes; Student Surveys; Synchronous Communication; Telecommunications; Tools; Undergraduate Students; __:import:01; __:match:final; __:matched; __:study_id:2096807; __finaldtb

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 ZenodoArchiveConcept: 14967647 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 2405685:4WMEPBIA
Keywords: _r:AddedByMyEducationEvidence

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14622107 ZenodoArchiveConcept: 14622106 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1085 2405685:KIEIX7NP
Keywords: _r:AddedByMyEducationEvidence

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Tanzanian Teachers’ Experiences of Teaching With Technology: Recommendations for policy and practice - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2022)
This policy brief reports on a teacher survey in Tanzania (July–November 2021) that EdTech Hub commissioned HakiElimu to conduct in order to inform the government’s ongoing national school-based TCPD reform. The survey items were taken from a landmark global survey of 20,000+ teachers’ reflections, experiences, and challenges concerning EdTech access and use, teaching and learning, and professional development over the preceding year, reported by a team from T4 Education and EdTech Hub. Keywords: Educational technology; learning outcomes; teacher needs; teacher professional development; teacher voice; technology access An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6543151 10.53832/edtechhub.0125 2405685:VNE3Q93U
Keywords: _r:AddedByZotZen

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013521521?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-017-9588-z 2339240:P4NQHVXZ 2405685:6WP3TDP7 2405685:UGF4PS66 2534378:9HNTLUFX 2534378:H8CJ8ZGT 2534378:V4VN2T5H
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers–Information Science And Information Theory; ERIC; Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

Improving educational outcomes & reducing absenteeism at remote villages with mobile technology and WhatsApp: findings from rural India - Nedungadi, Prema; Mulki, Karunya; Raman, Raghu (Education and Information Technologies, 2018)
Reduction of teacher and student absenteeism, together with consistent teacher support and training, are critical factors in improving the quality of education in rural India. As part of an ongoing project involving schools and educational centers in rural areas spread across 21 Indian states, this study investigated how implementation of two simple, accessible technologies could not only reduce absenteeism but also increase teachers' effectiveness and improve student performance. In addition to students and teachers, key stakeholders included educational coordinators who provided support and monitoring regarding use of WhatsApp and two additional apps designed specifically to support simple educational improvements. In our study we coded and analyzed nine months of messages (n = 8968), both photographs and texts, posted by 26 participants. The number of text messages related to attendance was strongly positively correlated with frequency of interactions between coordinators and teachers. Our approach resulted in increased teacher and student attendance, as well as improvements in lessons and other planned educational activities. This model functions well in rural settings where there is poor internet connectivity and lack of supporting infrastructure. Remote schools can easily adopt this tablet-based model to reduce teacher absenteeism, improve teaching techniques, improve educational resources, and increase student performance.
Publisher: Springer, 233 Spring Street, New York, NY 10013 Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2013521521?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-017-9588-z 2129771:FUJHTZ2D 2339240:KMCH965J 2339240:P4NQHVXZ 2339240:WE6J7JIZ 2405685:6WP3TDP7 2405685:KNKBHWBG 2405685:UGF4PS66 2405685:WF9JZ9QL 2534378:9HNTLUFX 2534378:H8CJ8ZGT 2534378:V4VN2T5H 4556019:7XRZPBHX
Keywords: Absenteeism; Academic Achievement; Attendance; Attendance Patterns; Computer Oriented Programs; Computers–Information Science And Information Theory; ERIC; Current Index to Journals in Education (CIJE); Educational Opportunities; Educational Quality; Educational technology; Foreign Countries; ICT; India; Monitoring; Quality of education; Rural Areas; Rural areas; Rural education; School education; Software; Students; Teacher Effectiveness; Teacher absence; Teacher monitoring; Teachers; Tele-education; WhatsApp; __:import:01; __:match:final; __:matched; __:study_id:2097863; __finaldtb

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7371460 ZenodoArchiveConcept: 7371459 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7371460 10.5281/zenodo.7473922 10.5281/zenodo.7500121 10.53832/edtechhub.0151 2339240:BE2J66WG 2405685:BBAPFKW4 2405685:JHWKC6F4 2405685:P833K7KC 2405685:YLS6YQ3U
Keywords: _r:AddedByZotZen

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15352737 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1112 ZenodoArchiveConcept: 15352736
Keywords: _r:AddedByMyEducationEvidence

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
ZenodoArchiveID: 4706062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706062 2339240:IB8GIAAB 2339240:VEARRJJL 2339240:XRVLW2AX 2405685:BR48DF69 2405685:IPAT355N 2405685:SDTIZDHS
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Demand-Driven Evidence Delivery and Uptake: Reflections on the Edtech Hub Helpdesk - Jordan, Katy; Thakrar, Jayshree; Patel, Prachi; Ramesh Vasudevan, Sharanya; Coflan, Caitlin; Thang, Sarah; Myers, Christina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13736013 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1056 ZenodoArchiveConcept: 13736012
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7341501 ZenodoArchiveConcept: 7341500 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7341501 10.53832/edtechhub.0138 2405685:E7C9MN3V
Keywords: _r:AddedByZotZen

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6981598 ZenodoArchiveConcept: 6981597 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6981598 10.53832/edtechhub.0105 2405685:BDT76583
Keywords: _r:AddedByZotZen

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.12571 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12571 2339240:9996TBZS 2405685:6XQNSME6

A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.12571 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.12571 2339240:9996TBZS 2405685:6XQNSME6

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7023230 ZenodoArchiveConcept: 7023229 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7023230 10.5281/zenodo.7038003 10.53832/edtechhub.0111 2405685:E2R8AXSA 2405685:SMH62I7W 2405685:VINQBTJ5
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Behaviour change key principles for EdTech | MASTER framework - Rahman, Asad; Carter, Alice; Wambûi Kuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries, to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool aims to help you get started with ways to design for innovation behaviours or mindsets and make them stick. Keywords: behavioural change; behavioural design; behavioural innovation; EdTech; innovation; sandbox; intervention design An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7245959 ZenodoArchiveConcept: 7245958 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7245959 10.53832/edtechhub.0129 2339240:UURNQTLM 2405685:6SXI2PS9 2405685:BT283J6U 2405685:KEFXIABC
Keywords: _r:AddedByZotZen

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6942540 10.53832/edtechhub.0103 2339240:Y9SQVEU9 2405685:77665EVG 2405685:JV4F45P5
Keywords: _r:AddedByZotZen

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10694591 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1014 ZenodoArchiveConcept: 10694590
Keywords: _r:AddedByMyEducationEvidence

Technology-Enabled Psychosocial Support Interventions for Education in Emergencies - Moustafa, Nariman; Mtungwa, Nothando (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15806037 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1128 ZenodoArchiveConcept: 15806036
Keywords: _r:AddedByMyEducationEvidence

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

An Investigation of the Impact of an Intervention to Reduce Academic Procrastination Using Short Message Service (SMS) Technology - Davis, D; Abbitt, J (Journal of Interactive Online Learning, 2013)
This mixed-method pilot study investigated the impact of a custom Short Message Service (SMS) reminder system developed to help students reduce procrastination and increase performance on weekly content-related quizzes in a high-enrollment hybrid online course. Text message reminders were sent to three students with high procrastination and low performance levels on a schedule based on free-operant avoidance principles, where messages would be terminated upon completion of the weekly quiz. The results suggest that there was sufficient evidence that the system had a positive effect on procrastination levels, but less evidence for an effect on performance. Subsequent interviews with the participants confirmed the utility and potential of the system, and revealed areas for improvement in the implementation of the SMS reminder system as well as an understanding of the students’ response to the intervention.
KerkoCite.ItemAlsoKnownAs: 2405685:GVZZTKW6
Keywords: ⛔ No DOI found

What Should Ministries of Education Prioritise When Crafting Their Edtech Strategies? - Thinley, Sangay (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at priorities for governments and ministries of education when crafting EdTech Strategies. Interest in developing EdTech strategies related to operational targets and outcomes has increased over the past few years, especially in response to the learning disruptions caused by the Covid-19 pandemic. Evidence suggests that countries with established EdTech strategies were better equipped to respond to the pandemic and its effects due to their advanced preparation and readiness for large-scale remote learning. We examine the key principles for EdTech strategies, including the importance of focusing on learning outcomes, inclusivity, teacher training, costs, and contextual needs, among other factors. We draw on EdTech Hub's work in supporting several governments in designing and implementing EdTech strategies, as well as broader evidence from the field, to offer practical insights. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt, such as prioritising consultative processes of strategy development while focusing on multi-modal, problem-driven EdTech solutions and interventions guided by a unifying educational goal. We highlight areas that require further research, in particular questions related to cost-effective approaches to improving global learning, how governments can develop dynamic and iterative strategies, and the role of private sector partnerships in the successful implementation of EdTech strategies. Keywords: EdTech; education technology; education strategy; best practices for EdTech; EdTech planning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13360175 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1054 ZenodoArchiveConcept: 13360174
Keywords: _r:AddedByMyEducationEvidence

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Can Text Message Nudges Improve Academic Outcomes in College? Evidence from a West Virginia Initiative - Castleman, Benjamin; Meyer, Katharine (The Review of Higher Education, 2020)
Although socioeconomic disparities in college enrollment have declined, gaps in college completion persist by income and geography. We investigate a text messaging campaign in West Virginia, which addressed informational barriers and behavioral obstacles to college persistence by providing college students with simplified information, encouragement, and access to individualized advising. Using descriptive and matching methods, we find participating students were more likely to remain enrolled throughout their first year of college, and completed more course credits with suggestive evidence of improved academic performance. This evidence suggests colleges play an important role communicating information about academic expectations, support resources, and norms.
KerkoCite.ItemAlsoKnownAs: 10.1353/rhe.2020.0015 2339240:NE7RSPVL 2339240:PR9DQ5AV 2405685:F5XK6CZS 2405685:MDMWTG3D 2405685:Z6KKY8ZV 2534379:LIY4MNF5

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13767575 ZenodoArchiveConcept: 13767574 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1050 10.53832/edtechhub.1060 2405685:K28H9QDG 2405685:ZAKFGN9M
Keywords: _r:AddedByMyEducationEvidence

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6760137 10.53832/edtechhub.0141 2405685:6VSSZYCK 2405685:KMQCABXM
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5803107 10.53832/edtechhub.0076 2405685:CI5UZ5R4 2405685:HU5IFEK9
Keywords: _r:AddedByZotZen

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
EdTechHub.Source: 2129771:I2CG3TP3 shortDOI: 10/ghgk6z KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.1204703 10/ghgk6z 2129771:I2CG3TP3 2129771:SI7RBL6P 2405685:46SDL9HI
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11235144 ZenodoArchiveConcept: 11235143 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1029 10.53832/edtechhub.1030
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10610797 ZenodoArchiveConcept: 10610796 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1007 2339240:SZE9FBW4 2405685:IIAMD77T
Keywords: _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Guide pour les administrateurs de la plateforme Formation À Distance - Rasolohery, Hasiniavo; Ranaivosamoelina, Tokiniaina (EdTech Hub, 2025)
This is a practical guide for administrators of the Formation À Distance (FAD) platform in Madagascar. The guide provides instructions on managing the platform, with a focus on evaluations and forums. It covers topics such as setting up different types of evaluations (quizzes, assignments), configuring forum settings, managing discussions, and moderating forums. It also includes best practices for both evaluations and forums, as well as security considerations. The document provides step-by-step instructions with screenshots for specific tasks like activating edit mode, adding activities or resources, setting up tests, and configuring forum parameters. It also includes a glossary of terms, references, and useful links. The guide is intended to help administrators effectively manage the FAD platform and support teachers and students in their online learning activities. Keywords: teacher professional development; Madagascar; Moodle; tablet; administrator guide Ceci est un guide pratique destiné aux administrateurs de la plateforme de Formation À Distance (FAD) à Madagascar. Il fournit des instructions pour la gestion de la plateforme, en mettant l’accent sur les évaluations et les forums. Il couvre des sujets tels que la configuration des différents types d’évaluations (quiz, devoirs), le paramétrage des forums, la gestion des discussions et la modération des forums. Il inclut également les meilleures pratiques pour les évaluations et les forums, ainsi que des considérations de sécurité. Le document propose des instructions détaillées, illustrées par des captures d’écran, pour des tâches spécifiques comme l’activation du mode édition, l’ajout d’activités ou de ressources, la mise en place de tests et le paramétrage des forums. Il comprend également un glossaire des termes, des références et des liens utiles. Ce guide vise à aider les administrateurs à gérer efficacement la plateforme FAD et à soutenir les enseignants et les élèves dans leurs activités d’apprentissage en ligne. Mots clés: formation pédagogique; Madagascar; Moodle; tablette; guide pour les administrateurs An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230806 ZenodoArchiveConcept: 14230805 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1062 10.53832/edtechhub.1074
Keywords: _r:AddedByMyEducationEvidence

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
ZenodoArchiveID: 4706036 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706036 2339240:CB8D4LUQ 2339240:METE88UD 2339240:MK55NVDC 2339240:Z3EF9Q75 2405685:3XIBJD8G 2405685:3Y33YNL3 2405685:8JZVGC6W 2405685:HBXKVKMA 2405685:QJ783WH5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7754059 ZenodoArchiveConcept: 7754058 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521858 10.5281/zenodo.7754059 10.53832/edtechhub.0161 2405685:6E2WK46K
Keywords: _r:AddedByZotZen

Education in Emergencies: A Rapid Evidence Review - Mitchell, Joel; Ashlee, Amy; Clericetti, Giulia; Gladwell, Jessica; Torrance, Rebecca (EdTech Hub)
PreviousDOI: 10.5281/zenodo.4476897 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4476897 10.5281/zenodo.4556940 2339240:GU8FEH69 2339240:W9GJBGT9 2405685:FEXJQ37Q 2405685:ZPTMAP5C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

Sandbox Handbook V.2.0 - EdTech Hub (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7019219 ZenodoArchiveConcept: 7019218 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7019219 10.53832/edtechhub.0108 2339240:LNQBY8R8 2405685:49ZFP7UN 2405685:MP7LCGPN
Keywords: _r:AddedByZotZen

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396237 10.53832/edtechhub.0086 2405685:CVS2WZC3 2405685:FVSQD8MB
Keywords: F: Helpdesk response; _r:AddedByZotZen

Designing Digital Notifications to Support Teacher Uptake of Data Dashboards - Sun, Chen; Daltry, Rebecca; Major, Louis; Friedberg, Aidan (EdTech Hub, 2025)
This is the fourth in a series of evidence briefs, reporting on four A/B/n tests which explore different features to enhance digital personalised learning (DPL) tools. This brief investigates the extent to which the provision of notifications to pre-primary teachers to view data dashboards impacts learner device usage and learning outcomes. The A/B/C test found no impact on device usage and negligible impact on learning outcomes. This suggests that accompanying data dashboards with notifications did not influence pedagogical practice in a way which impacted on learning. Recommendations for DPL providers and researchers are discussed, taking into account contextual factors. Keywords: low- and middle-income countries; digital personalised learning; pre-primary education; classroom-integrated implementation; notification system An output of EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13117643 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1049 ZenodoArchiveConcept: 13117642
Keywords: _r:AddedByMyEducationEvidence

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15366685 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1113 ZenodoArchiveConcept: 15366684
Keywords: _r:AddedByMyEducationEvidence

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
ZenodoArchiveID: 4556935 PreviousDOI: 10.5281/zenodo.4476991 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3956366 10.5281/zenodo.3956366 10.5281/zenodo.4476991 10.5281/zenodo.4556935 2259720:BFY7A76P 2339240:3WZUWHB3 2339240:CVI8639W 2339240:G8MSWBJC 2339240:IF3IMDSW 2339240:NUYRVP8T 2339240:UXMEFECL 2405685:BVXSZ7G4 2405685:BZFLWXG6 2405685:DPRU64AB 2405685:FMULV6ZI 2405685:TJ95P4G4 2405685:UJF6X47J 2405685:UVB294JN 2405685:Y3XDX8FW 4803016:WC4XVPPN
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5721401 10.53832/edtechhub.0070 2339240:CHJR9D5G 2339240:RFJZSHMG 2405685:FE3VBQQW 2405685:NFXKD34I 2405685:PU8D6GXN 2405685:SY9TIAMH
Keywords: _r:AddedByZotZen

Enquête nationale sur la possession et les usages des technologies parmi les enseignants du primaire - Rasolohery, Hasiniavo; Mitchell, Joel (EdTech Hub, 2025)
This document presents a report of a national survey on technology ownership and usage among primary school teachers in Madagascar, conducted in 2023. The survey, a collaboration between EdTech Hub, the National Institute of Pedagogical Training (INFP), and the Ministry of National Education, aimed to gather reliable data on ICT deployment across Madagascar's 23 regions. Data was collected through quantitative surveys and qualitative focus groups involving 1403 educators. Key findings reveal that while 97% of educators own technological tools, basic mobile phones are most prevalent. Smartphone ownership is significant, but usage is largely limited to calls and SMS, indicating underutilisation of advanced features. Internet access is limited, with only 25.2% of teachers accessing it via smartphone. Electricity access is relatively high at 89%, primarily through the national grid and solar energy. The report highlights the need for ICT training to enhance teachers' digital skills and recommends deploying offline systems to overcome connectivity issues. It also emphasises adapting content for teachers with disabilities and considering the predominantly regional language usage in professional settings. Keywords: national teacher survey; technology access; technology use; Madagascar; primary school Ce document présente un rapport sur une enquête nationale menée en 2023 sur la possession et l’usage des technologies par les enseignants du primaire à Madagascar. Cette enquête, réalisée en collaboration entre EdTech Hub, l’Institut National de Formation Pédagogique (INFP) et le Ministère de l’Éducation Nationale, visait à recueillir des données fiables sur le déploiement des TIC dans les 23 régions du pays. Les données ont été collectées à travers des enquêtes quantitatives et des groupes de discussion qualitatifs impliquant 1 403 enseignants. Les résultats clés révèlent que, bien que 97 % des enseignants possèdent des outils technologiques, les téléphones mobiles basiques sont les plus répandus. La possession de smartphones est significative, mais leur utilisation se limite principalement aux appels et aux SMS, ce qui indique une sous-utilisation des fonctionnalités avancées. L’accès à Internet reste limité, avec seulement 25,2 % des enseignants l’utilisant via un smartphone. L’accès à l’électricité est relativement élevé (89 %), principalement via le réseau national et l’énergie solaire. Le rapport souligne la nécessité d’une formation aux TIC pour améliorer les compétences numériques des enseignants et recommande le déploiement de systèmes hors ligne pour pallier les problèmes de connectivité. Il met également l’accent sur l’adaptation des contenus aux enseignants en situation de handicap et sur la prise en compte de l’usage majoritaire des langues régionales dans les environnements professionnels. Mots clés: enquête nationale des enseignants; accès à technologie; utilisation de technologie; Madagascar; Moodle; école primaire An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995637 ZenodoArchiveConcept: 14995636 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7997034 10.5281/zenodo.7997057 10.5281/zenodo.8401936 10.53832/edtechhub.1100 2405685:4MWP8553 2405685:5DJ69UTD
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
ZenodoArchiveID: 4706019 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706019 2339240:D85SY35R 2405685:SMLIMS2X
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Embracing EdTech: four critical questions answered through a rapid prototype programme on teachers’ professional development (TPD) - Sabbab, Salman; Shakil, Abdullah All; Alam, Faria (EdTech Hub, 2021)
Seventy-one teachers participating in the ‘Onneshon’ prototype were flooding the WhatsApp group with messages about the challenges and hiccups they were experiencing, either with watching the video content or with taking a quiz in the first two weeks. Problems were pouring in and so were solutions being innovated and offered through diverse channels. In the space of two weeks, the…
KerkoCite.ItemAlsoKnownAs: 2405685:ZWUKU2YL
Keywords: _EdTechHub_Output

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14172051 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1069 ZenodoArchiveConcept: 14172050
Keywords: _r:AddedByMyEducationEvidence

The Sandbox Model: A Novel Approach to Iterating while Implementing an Emergency Education Program in Lebanon during the COVID-19 Pandemic - Boujikian, Michèle; Carter, Alice; Jordan, Katy (2022)
Jusoor’s Refugee Education Program helps Syrian refugee children living in Lebanon integrate back into formal schooling. When schools closed due to the COVID-19 pandemic, the refugee program adapted to distance learning by developing Azima, a novel program that used WhatsApp to enable children to keep learning. Azima had to respond immediately to the emergency context while maintaining high education standards, and it also needed to find an effective way to test and refine its content quickly. To do this, the Azima program adopted an innovative experimental approach called a sandbox. A sandbox model operates in rapid iterative cycles and uses multiple methods to quickly test a program’s assumptions about how it will meet its goals. In this field note, we use Azima as a case study to report on our experience of applying the sandbox model. We reflect on the benefits and limitations of this novel approach in supporting the use of education technology in a crisis situation.
Accepted: 2022-11-07T13:27:21Z Publisher: Inter-agency for Education in Emergencies (INEE) KerkoCite.ItemAlsoKnownAs: 10.33682/rj45-k7z7 2405685:LDWAQKHF

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
ZenodoArchiveID: 5652135 previousDOI: 10.5281/zenodo.3906041 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3906041 10.5281/zenodo.5652135 2339240:546TH9C9 2339240:E5AXYSMF 2339240:RKVKV84H 2405685:4ER9WB55 2405685:7JSP4PFC 2405685:DMSLLEQV 2405685:HZ5X5A4W 2405685:V44Z75Z3 2405685:VVB3BRE5
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6475261 10.53832/edtechhub.0090 2405685:DSG9QF4F 2405685:GBQT3KMA
Keywords: _r:AddedByZotZen

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14648336 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1087 ZenodoArchiveConcept: 14648335
Keywords: Hide; _r:AddedByMyEducationEvidence

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4780972 2405685:4UQT8WRN 2405685:WWUQ7VRT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5654887 10.53832/edtechhub.0067 2339240:VNTPMCJQ 2339240:XLHSGBDA 2405685:FSVST5BF 2405685:HVDCZZVG 2405685:L5WPA5SN 2405685:YWENAQDF
Keywords: _r:AddedByZotZen

Note de conseils sur la plateforme numérique - Messa, Angele; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2025)
This document is a guidance note on digital platforms, specifically focusing on e-learning and the use of Opale and Moodle software. It aims to support the implementation of a digital learning platform in Madagascar. The report addresses questions and challenges faced by the Ministry of National Education in developing and deploying digital educational content. It covers various aspects of e-learning, including evaluation methods, content structuring, accessibility, interactivity, and technical requirements. Key topics include different evaluation models, types of e-learning evaluation (formative and summative), guidelines for using Opale, tablet specifications for online learning, ensuring course accessibility, and using Moodle both online and offline. The document also provides a checklist for ensuring quality in e-learning course development and implementation. Keywords: e-learning; Moodle; Opale; digital platform; accessibility; usability; Madagascar Ce document est une note d’orientation sur les plateformes numériques, avec un accent particulier sur l’e-learning et l’utilisation des logiciels Opale et Moodle. Il vise à soutenir la mise en place d’une plateforme d’apprentissage numérique à Madagascar. Le rapport aborde les questions et défis rencontrés par le Ministère de l’Éducation Nationale dans le développement et le déploiement de contenus éducatifs numériques. Il traite de divers aspects de l’e-learning, notamment les méthodes d’évaluation, la structuration des contenus, l’accessibilité, l’interactivité et les exigences techniques. Les principaux sujets incluent les différents modèles d’évaluation, les types d’évaluation en e-learning (formative et sommative), les recommandations pour l’utilisation d’Opale, les spécifications des tablettes pour l’apprentissage en ligne, l’accessibilité des cours et l’utilisation de Moodle en mode en ligne et hors ligne. Le document propose également une liste de contrôle pour garantir la qualité du développement et de la mise en œuvre des cours en e-learning. Mots clés: e-learning; Moodle; Opale; platforme numériques; accessibilité; usabilité; Madagascar An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14995952 ZenodoArchiveConcept: 14995951 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7303773 10.53832/edtechhub.1101 2405685:RMJK6G6Q
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7003826 ZenodoArchiveConcept: 7003825 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7003826 10.53832/edtechhub.0118 2339240:3XB6YUXL 2405685:GXLAGDUM 2405685:RPR47JXT 2405685:ZXBB58KS
Keywords: _r:AddedByZotZen

Distance learning in the context of COVID-19: the case of Rwanda - Ngabonzima, Ernest; Isimbi, Roberte; Mwali, Marie Merci; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4706016 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706016 2339240:F62THLX3 2339240:V5PQVKX2 2405685:ADNJFTFA 2405685:CMDUS73G 2405685:T2JBHFBC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7106003 ZenodoArchiveConcept: 7106002 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7106003 10.53832/edtechhub.0119 2405685:Y3SBIPF9 2405685:ZVX4DTXQ
Keywords: _r:AddedByZotZen

China: testing a decade of online education preparation - Liangdi, Xu; Groenewegen-Lau, Jeroen (EdTech Hub, 2020)
ZenodoArchiveID: 4705990 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705990 2339240:S2B995E4 2405685:P5B4YWID
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5604677 10.5281/zenodo.5761966 10.53832/edtechhub.0069 2405685:CPP3A2WM 2405685:DM8N3E8E 2405685:PXUQJZTH
Keywords: Helpdesk Response; _r:AddedByZotZen

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Place: Cambridge Publisher: Cambridge University Press Cam URL: https://ezp.lib.cam.ac.uk/login?url=https://search.proquest.com/docview/2084810389?accountid=9851 KerkoCite.ItemAlsoKnownAs: 10.1017/S0958344017000349 2405685:WM42S327 2534378:59HFNMGI 2534378:A5Y5932K 2534378:EEFLCSXC 2534378:G3TW72LP
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction–CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC; Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics–Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

Rapport d’Observation du Testing Alpha - Ranaivosamoelina, Tokiniaina; Rasolohery, Hasiniavo; Koomar, Saalim (EdTech Hub, 2025)
This document, details the Alpha user testing of a digital learning platform and educational applications for the Ministry of National Education of Madagascar, aimed at training 2000 teachers. Conducted in July 2024, the testing focused on functionality and accessibility. Twenty-nine testers, primarily web developers and instructional designers, used a Google Forms questionnaire to evaluate the platform and applications. The results showed that while the platform was generally functional, with most features validated, several areas needed adjustments, particularly in accessibility and specific functions like the quiz timer. The applications had more issues, with several features requiring fixes and accessibility being a significant concern. Key recommendations included diagnosing and fixing defective parts, restructuring modules for better accessibility, optimising multimedia file sizes, and creating a detailed user guide. The testing highlighted the need for improvements before the Beta testing phase with teachers. Keywords: teacher professional development; Madagascar; Moodle; user testing Ce document détaille les tests utilisateurs en phase Alpha d’une plateforme d’apprentissage numérique et d’applications éducatives développées pour le Ministère de l’Éducation Nationale de Madagascar, dans le cadre de la formation de 2 000 enseignants. Réalisés en juillet 2024, ces tests ont porté sur la fonctionnalité et l’accessibilité. Vingt-neuf testeurs, principalement des développeurs web et des concepteurs pédagogiques, ont évalué la plateforme et les applications via un questionnaire Google Forms. Les résultats ont montré que, bien que la plateforme soit globalement fonctionnelle avec la plupart des fonctionnalités validées, plusieurs ajustements étaient nécessaires, notamment en matière d’accessibilité et pour certaines fonctions spécifiques comme le minuteur des quiz. Les applications présentaient davantage de problèmes, plusieurs fonctionnalités nécessitant des corrections et l’accessibilité étant un défi majeur. Les principales recommandations incluaient le diagnostic et la correction des éléments défectueux, la restructuration des modules pour une meilleure accessibilité, l’optimisation de la taille des fichiers multimédias et la création d’un guide utilisateur détaillé. Ces tests ont mis en évidence la nécessité d’améliorations avant la phase de test Beta avec les enseignants. Mots clés: formation pédagogique; Madagascar; Moodle; test utilisateur An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14230731 ZenodoArchiveConcept: 14230730 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1035 10.53832/edtechhub.1071
Keywords: _r:AddedByMyEducationEvidence

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

A Theory of Change for Teachers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Ahmed, Shakil; Kaye, Tom; Zubairi, Asma (EdTech Hub, 2022)
The second of a trilogy of Theories of Change (TOCs) that focuses on teachers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how teachers’ professional learning experiences will enable them to support learners in ways that take advantage of available technology. The TOC is a useful tool to support the design, implementation, and evaluation of all programmes and initiatives that are designed for teachers, and aim to improve educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; teachers' professional development; education An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6400980 10.53832/edtechhub.0086 10.53832/edtechhub.0088 2405685:29Z2JFJT 2405685:CB5GGAXU
Keywords: _r:AddedByZotZen

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10599846 ZenodoArchiveConcept: 10599845 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1004 2339240:VBH94XQQ 2405685:DJRV7KZW
Keywords: _r:AddedByMyEducationEvidence

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The Effect of Teacher-Family Communication on Student Engagement: Evidence from a Randomized Field Experiment - Kraft, M; Dougherty, Shaun (Journal of Research on Educational Effectiveness, 2013)
In this study, we evaluate the efficacy of teacher communication with parents and students as a means of increasing student engagement. We estimate the causal effect of teacher communication by conducting a randomized field experiment in which sixth- and ninth-grade students were assigned to receive a daily phone call home and a text/written message during a mandatory summer school program. We find that frequent teacher–family communication immediately increased student engagement as measured by homework completion rates, on-task behavior, and class participation. On average, teacher–family communication increased the odds that students completed their homework by 40%, decreased instances in which teachers had to redirect students’ attention to the task at hand by 25%, and increased class participation rates by 15%. Drawing upon surveys and interviews with participating teachers and students, we identify three primary mechanisms through which communication likely affected engagement: stronger teacher–student relationships, expanded parental involvement, and increased student motivation.
KerkoCite.ItemAlsoKnownAs: 10.1080/19345747.2012.743636 2339240:3H26G6RN 2339240:X9LRSMNV 2405685:7HER36AG 2405685:BXJPVKUP 2405685:WYAJLA9C 2534379:82ZR3C22
Keywords: ___working_potential_duplicate

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
previousDOI: 10.5281/zenodo.3960140 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3960140 10.53832/edtechhub.0027 2339240:6E8ZDLYB 2339240:Z28GJH3E 2405685:6TJ92NFH 2405685:6XEEQHVU 2405685:8CB5PTUQ 2405685:EERE25UX 2405685:FQKKVE4W 2405685:K4DEZSCM 2405685:L4ULUSCB 2405685:NTMUHEW9 2405685:S4VEIC5W 2405685:W7SY73AT
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
ZenodoArchiveID: 4556925 PreviousDOI: 10.5281/zenodo.3948175 PreviousDOI: 10.5281/zenodo.4477170 PreviousShortDOI: 10/gg7sp2 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948175 10.5281/zenodo.3948174 10.5281/zenodo.3948175 10.5281/zenodo.4477170 10.5281/zenodo.4556925 2339240:6NYL4Q6K 2339240:782897NS 2339240:CQIWZXYK 2339240:FFVXKB6Y 2339240:FH2WAXTQ 2339240:KAWEDEAZ 2339240:L9THHN3N 2339240:P8B4HPZC 2339240:QLA593HB 2339240:T58E6LDA 2339240:T8L6PTRX 2339240:VZBB4HAF 2405685:839AFBBS 2405685:89H7NAA7 2405685:A2II5ZV7 2405685:A49KTEL6 2405685:AT6JS3QN 2405685:CJR7PMKJ 2405685:DEXS2WA8 2405685:FFSBB3JJ 2405685:NQSPAG3I 2405685:RVZFVD7G 2405685:U95XV67E 2405685:WJRBJQBN 2534378:8FA5G2KF
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5813529 10.53832/edtechhub.0084 2405685:DPWSAA9Z
Keywords: _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Jordan’s EdTech response to COVID-19 - Al-Hindawi, Hind; Hashem, Lina (EdTech Hub, 2020)
ZenodoArchiveID: 4706057 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706057 2339240:7DDCIKY9 2339240:P8XVRD6S 2405685:BTX9XW3J 2405685:KNCXGVW3 2405685:XFBMF3QV
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

A Quasi-Experimental Study of the Classroom Practices of English Language Teachers and the English Language Proficiency of Students, in Primary and Secondary Schools in Bangladesh - Power, Tom; McCormick, Robert; Asbeek-Brusse, Elsbeth (2017)
English in Action (EIA) is an English language teacher development project based in Bangladesh that was intended to run from 2008 to 2017, but which was extended at the request of the Government of Bangladesh, with additional funding from UKAID, for a further year to 2018. By the time of the design of this study (2014-2015) EIA was drawing to the end of upscaling (phase III, 2011-2014) and entering institutionalisation and sustainability (phase IV, 2014-17, extended 2018). Successive prior studies had indicated substantial success in improving both teachers’ classroom practices and student learning outcomes, over the pre-project baseline (e.g. EIA 2011, 2012). The 2014 Annual Review of EIA recommended that in the final phase, EIA should explore whether it would be possible to carry out a study that compared a ‘counterfactual’ or control-group of teachers and students, to the ‘EIA’ or treatment schools: i.e. a Randomised Control Trial or Quasi-Experimental study. A proposal for a Quasi-Experimental study was developed in collaboration with DFID’s South Asia Research Hub (SARH), which also provided the additional funding necessary to implement such a study. The teachers and students who were the subject of this study, were the fourth cohort to participate in English in Action (together with teachers from ‘control’ schools, in the same Upazilas). This fourth EIA cohort included Schools, Teachers and Students from approximately 200 Upazilas (of approximately 500 in total) across Bangladesh, including some of the most disadvantaged areas (with reference to UNICEF deprivation index), such as Char, Hoar and Monga districts. Teachers took part in a school-based teacher development Programme, learning communicative language teaching approaches through carrying out new classroom activities, guided by teacher development videos that showed teachers, students and schools similar to those across the country. Teachers also had classroom audio resources for use with students. All digital materials were available offline, on teachers own mobile phones, so there is no dilution of the Programmes core messages about teaching and learning, by some intermediary coming between the teacher and the materials. Teachers were supported through these activities, by other teachers in their schools, by their head teachers and by local education officers. Some teachers from each area were also given additional support and guidance from divisional EIA staff, to act as Teacher Facilitators, helping teachers work through activities and share their experiences at local cluster meetings. Whereas previous cohorts of teachers had attended eight local teacher development meetings over their participation in the project, for Cohort Four, this was reduced to four meetings, with a greater emphasis being placed on support in school by head teachers, as well as support from local education officers. This change was part of the move towards institutionalisation and sustainability of project activities within and through government systems and local officers. The purpose of this study was both to provide the evaluation evidence required for the final phase of the EIA project and to contribute to the international body of research evidence on effective practices in teacher development in low-to-middle income country contexts.
Place: Dhaka, Bangladesh Publisher: English in Action (EIA) KerkoCite.ItemAlsoKnownAs: 2339240:5ASMY75P 2405685:GJV2BMAG

Evaluation of the Transformative Potential of Positive Gender Socialization in Education for Peace Building. - Chinen, Marjorie; Elmeski, Mohammed (Society for Research on Educational Effectiveness, 2016)
American Institutes for Research (AIR) is conducting an impact evaluation of The United Nations Children's Emergency Fund's (UNICEF's) teacher-training program and reinforcing text messages that aim to provide meaningful knowledge regarding the transformative potential of positive gender socialization in education for peace building in the region of Karamoja, Uganda. The impact evaluation assesses the effects of the teacher-training program, with an emphasis on gender socialization, on teachers' knowledge, attitudes, and practices concerned with gender equity, and positive gender socialization. The authors implemented a mixed-methods research design for the impact evaluation, using quantitative and qualitative methods. They compared the outcomes of interest among the teachers who benefit from the program with the outcomes of interest of comparable teachers in different schools who do not benefit from the program. The impact evaluation is based on an eight-month intervention, with baseline data collected in March 2015 and endline data collected in November 2015. One hundred five schools from eight Coordinating Centre Tutors (CCTs) located in the districts of Abim, Kaabong, and Napak are participating in the study, with a third of the schools receiving the training plus reinforcing text messages (the "complete intervention" group), another third receiving the teacher training only (the "limited intervention" group), and the other third not receiving any of the interventions (the control or "business as usual" group). A total of 916 teachers working in the 105 schools at the time of baseline data collection were surveyed. Provided that the various stakeholders respond in the manner anticipated, the trainings–and potentially the active teacher support and engagement delivered using the mobile SMS platform–should lead to a set of initial effects or intermediate outcomes. Tables and figures are appended.
KerkoCite.ItemAlsoKnownAs: 2339240:MAP7CBL4 2405685:N7W75YR3 2405685:ZS4NGWQB 2534378:NLJUTVDT 2534378:QEDQMKYP
Keywords: Comparative Analysis; ERIC; Resources in Education (RIE); Educational Practices; Elementary Education; Elementary School Teachers; Foreign Countries; Inservice Teacher Education; Intervention; Mixed Methods Research; Outcome Measures; Peace; Program Effectiveness; Randomized Controlled Trials; Sex Fairness; Socialization; Synchronous Communication; Teacher Attitudes; Teacher Characteristics; Telecommunications; Uganda; __:import:01; __:match:final; __:matched; __:study_id:2097972; ___working_potential_duplicate; __finaldtb; ⛔ No DOI found

Evaluation of the transformative potential of positive gender socialization in education for peace building - Chinen, Marjorie; Elmeski, Mohammed (Society for Research on Educational Effectiveness, 2016)
American Institutes for Research (AIR) is conducting an impact evaluation of The United Nations Children's Emergency Fund's (UNICEF's) teacher-training program and reinforcing text messages that aim to provide meaningful knowledge regarding the transformative potential of positive gender socialization in education for peace building in the region of Karamoja, Uganda. The impact evaluation assesses the effects of the teacher-training program, with an emphasis on gender socialization, on teachers' knowledge, attitudes, and practices concerned with gender equity, and positive gender socialization. The authors implemented a mixed-methods research design for the impact evaluation, using quantitative and qualitative methods. They compared the outcomes of interest among the teachers who benefit from the program with the outcomes of interest of comparable teachers in different schools who do not benefit from the program. The impact evaluation is based on an eight-month intervention, with baseline data collected in March 2015 and endline data collected in November 2015. One hundred five schools from eight Coordinating Centre Tutors (CCTs) located in the districts of Abim, Kaabong, and Napak are participating in the study, with a third of the schools receiving the training plus reinforcing text messages (the "complete intervention" group), another third receiving the teacher training only (the "limited intervention" group), and the other third not receiving any of the interventions (the control or "business as usual" group). A total of 916 teachers working in the 105 schools at the time of baseline data collection were surveyed. Provided that the various stakeholders respond in the manner anticipated, the trainings–and potentially the active teacher support and engagement delivered using the mobile SMS platform–should lead to a set of initial effects or intermediate outcomes. Tables and figures are appended.
Publication Title: Society for Research on Educational Effectiveness Loc in Archive 1826527485; ED567431 Extra URL: https://www.peace-ed-campaign.org/evaluation-transformative-potential-positive-gender-socialization-education-peacebuilding/ KerkoCite.ItemAlsoKnownAs: 2339240:WKT3G6D8 2405685:BDVXUH5G 2534378:NLJUTVDT 2534378:QEDQMKYP
Keywords: Comparative Analysis; ERIC; Resources in Education (RIE); Educational Practices; Elementary Education; Elementary School Teachers; Foreign Countries; Inservice Teacher Education; Intervention; Mixed Methods Research; Outcome Measures; Peace; Program Effectiveness; Randomized Controlled Trials; Sex Fairness; Socialization; Synchronous Communication; Teacher Attitudes; Teacher Characteristics; Telecommunications; Uganda; __:import:01; __:match:final; __:matched; __:study_id:2097972; __finaldtb

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FY4BHGH3

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0115 2339240:3KZX9ARU 2405685:BBQE9QUM 2405685:UUDK52LQ 2405685:YB52PCMQ
Keywords: ⛔ No INSPIRE recid found

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

What-are-countries-that-already-use-remote-learning-doing-and-what-can-we-learn-from-them-EdTechHub.pdf
KerkoCite.ItemAlsoKnownAs: 2405685:NLH4548E

Prospects of media education: Children empowerment through media literacy by the parents - Naseer, Rehana; Ahmed, Munib; Moazzam, Munawar (Pakistan Journal of Educational Research, 2022)
Media not only in Pakistan but all over the world have become the most influential and dominant source of information and entertainment. With the growing number of electronic gadgets, the device usage has been an indispensable component of these digitally aged children without which they feel their lives incomplete. The vast majority of children spend the significant amount of time using media devices in order to gratify their social needs and to gain information and entertainment, but its impact on young children is certainly undeniable. In relation to this context, the role of parents would be considered highly important in monitoring their children media-related activities. The in-depth interviews from parents of children aged between 8-13 years from Islamabad were conducted to understand their perceptions regarding the media related activities of their children, their mediation strategies, their key concerns, their awareness of media literacy, its significance value for children and their willingness to implement media literacy in educational curriculum for their children empowerment. The key finding indicates that advocating for initiation and implementation of media literacy education will be beneficial and enhance critical thinking skills among children to understand and evaluate media content and messages. Empowering children through media literacy education can address the major serious concerns of parents because restriction or limitation of children media usage is no longer effective. Hence, this study suggests that the engagement and active participation of children with these devices should be encouraged in a productive style. This study proposes that a high level of parental monitoring occurs when children use devices. Parents should monitor their children device usage. This recommends that parents need to have discussions with their children regarding their media related activities, because they are always worried about their children media usage both in school and at in home.
KerkoCite.ItemAlsoKnownAs: 10.52337/pjer.v5i1.430 2339240:7WRP2B7I 2405685:SADU9QUR

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
ZenodoArchiveID: 4749654 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749654 2405685:39XPD5EM 2405685:QZ2FJC4E
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:T7BK22I4

What does the research suggest is best practice in pedagogy for remote teaching? - McAleavy, Tony; Gorgen, Kristine (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:89I7MWHD 2405685:XHIZKSIA
Keywords: ___working_potential_duplicate; ⛔ No DOI found

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged